PENGARUH KOMUNIKASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DI MEDIASI OLEH MOTIVASI KERJA PADA BADAN PENGAWAS PEMILIHAN UMUM KABUPATEN KUANTAN SINGINGI - Kurniawan, Arif; Sasmita, Jumiati; Samsir, Samsir (Jurnal Daya Saing, 2023)
This study aims to look at the direct and indirect effects of communication and competence on employee performance mediated by work motivation at the General Election Supervisory Board of Kuantan Singingi Regency. This research was conducted at the Election Supervisory Board in Kuantan Singingi Regency. The approach used is quantitative. The population in this study were employees at the General Election Supervisory Board of Kuantan Singingi Regency, totaling 174 people. The sample is part of the population that has relatively the same characteristics and can be considered to represent the population using the Slovin technique so that the sample obtained with the Slovin formula is 121 samples. In distributing the questionnaires, the sampling method in this study used the Stratified Random Sampling technique. The results in this study say that Communication and Competence have a significant effect on work motivation. Communication, competence and work motivation have a significant effect on employee performance. Communication has a significant effect on employee performance. Work motivation is able to mediate the effect of communication and competence on employee performance.